A Semantic Analysis of Referential Expressions in NIKI Zefanya’s Album: Buzz - Tiodame Layupa Simanullang; Rafi Ryandieka Adinulhaq; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study explores the use of referential expressions in six selected songs from NIKI Zefanya’s 2024 album Buzz. Using a qualitative descriptive method and Halliday and Hasan’s theory of reference, the research aims to identify the types of referential expressions used in the lyrics and analyze their contribution to meaning and emotional impact. The findings reveal a total of 74 referential expressions, consisting of 53 personal references, 9 demonstrative references, and 12 comparative references. Personal references, such as I, you, and my, are the most dominant and function to express intimacy, personal emotion, and connection with the listener. Demonstrative references, like this and that, help point to emotional states or symbolic meanings. Comparative references, including like, better, and too much, are used to express metaphor, contrast, or emotional intensity. The study concludes that referential expressions not only serve grammatical functions but also shape how meaning is constructed in song lyrics. These expressions enhance narrative clarity, emotional depth, and listener engagement, showing that even small linguistic choices can have a strong impact on how music is experienced and understood.